Women in Latin American Academia: Gender Inequalities in the Social Sciences of Chile, Mexico, Brazil, and Argentina - Lube Guizardi, Menara (2024)
This article discusses the gender inequality female researchers and university professors face in the social sciences in four Latin American countries: Chile, Mexico, Brazil, and Argentina. The objective is to understand the forms of discrimination these women face in their work environment and analyze how these forms operate and impact their labor marginalization. It also seeks to characterize the difficulties faced by female academics in reconciling their reproductive and care responsibilities with professional practice. The second section sets out the theoretical framework and defines the concept of gender inequality. The third analyzes the gender gap in international academia, contrasting the most recent data from the Global North and South on the obstacles faced by women in professional academic settings. The fourth reviews case studies in Chile, Mexico, Brazil, and Argentina and offers a characterization of this problem in these countries. The final section presents four analytical-interpretative conclusions.